First record of the freshwater jellyfish Craspedacusta sowerbii Lankester, 1880 in Greece suggests distinct European invasion events - Karaouzas, Ioannis (2015)
This contribution presents the first record of the freshwater jellyfish Craspedacusta sowerbii Lankester, 1880 in Greece. The species was found in a water transfer canal adjacent to Lake Marathon, 45 km northeast of Athens; this is the southernmost record of this invasive alien medusa in the Balkan Peninsula and Europe. A review of recently published records shows that this species has expanded its range in Europe and the Mediterranean countries. Genetic analysis of the Greek specimen suggests that the phylogeny of C. sowerbii needs further evaluation since we are probably dealing with a distinct species within the genus Craspedacusta, and that the Greek population represents a distinct invasion event from that previously recorded in central Europe. However, due to a lack of molecular information on the native and invasive ranges, further phylogenetic studies are necessary to clarify this issue.